DEVELOPING CONSELOREE TO SUPPORT THESIS SUPERVISION PROCESS - Muhtadin, Khairul; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2021)
This research was conducted to develope Conseloree; an application to support thesis guidance process. The purpose of this research is to develop an innovative web-based application to support thesis guidance process at English Education Study Program. The form of this research is developmental research. The method of this research consists of three phases namely analyzing, designing and developing or called ADD. Analyze phase found that the difference busyness become problem to have a face to face meeting. Design phase was done to prepare the appropriate material to create the application. Develop phase was done to create an essential part of the conseloree. The designed product was completed after have an expert validation regarding to the needs and already stated valid to be use by the expert validator. The Conseloree considering the function, responsiveness, practical use and security. To sum up, it was found that Conseloree is usable to support thesis guidance process.